Laryngeal dissection and phonosurgical atlas - Klein, Adam M.; Johns, Michael M., III (Plural Publishing, 2009)
This superbly illustrated atlas provides laryngologists with the base skills required to undertake all kinds of laryngeal phonosurgery procedures, prior to testing out one's skill set in the operating room or office on real patients. It guides the reader through the anatomy and physiology of the larynx (as they relate to the procedures) and various office and O.R.-based phonosurgical procedures, using easy-to-follow instructions and labeled photos. As such, otolaryngologists and otolaryngologists-in-training can confidently rely on this new resource to aid in honing their skills in a comfortab.